An Overview of the Health Benefits, Extraction Methods and Improving the Properties of Pomegranate - Giada Benedetti; Federica Zabini; Luca Tagliavento; Francesco Meneguzzo; Vincenzo Calderone; Lara Testai (Antioxidants, 2023)
Pomegranate (Punica granatum L.) is a polyphenol-rich edible food and medicinal plant of ancient origin, containing flavonols, anthocyanins, and tannins, with ellagitannins as the most abundant polyphenols. In the last decades, its consumption and scientific interest increased, due to its multiple beneficial effects. Pomegranate is a balausta fruit, a large berry surrounded by a thick colored peel composed of exocarp and mesocarp with edible arils inside, from which the pomegranate juice can be produced by pressing. Seeds are used to obtain the seed oil, rich in fatty acids. The non-edible part of the fruit, the peel, although generally disposed as a waste or transformed into compost or biogas, is also used to extract bioactive products. This review summarizes some recent preclinical and clinical studies on pomegranate, which highlight promising beneficial effects in several fields. Although further insight is needed on key aspects, including the limited oral bioavailability and the role of possible active metabolites, the ongoing development of suitable encapsulation and green extraction techniques enabling the valorization of waste pomegranate products point to the great potential of pomegranate and its bioactive constituents as dietary supplements or adjuvants in therapies of cardiovascular and non-cardiovascular diseases.